(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Theimportant environmental friendly habit of the respondents taken under study bythe researcher is the habit of using communication media sources. Municipalityhas placed communication media sources of different colours at various publiclocations. The objective behind keeping these communication media sources is toreceive waste from the people in segregated form so that recycling of waste isachieved at an efficient level. The habit of using dustbin is furtherstatistically analyzed with different variables under study. The Figures88-104shows the significance of relationship between habit of the respondents to usepublic dustbin and different attributes of the study.